THE EFFECT OF SERVICE QUALITY AND MARKETING MIX STRATEGY ON SATISFACTION AND LOYALTY OF KPR CUSTOMERS AT PT. BANK CENTRAL ASIA, TBK. MAKASSAR BRANCH - Mardin Setiawan; Syamsu Alam; Jumidah Maming (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
This study aims to know and to analyze the effect of service quality strategy, marketing mix strategy on Household Loan Credit (KPR) customer satisfaction, the influence of service quality and marketing mix strategy on KPR customer loyalty, the effect on satisfaction on KPR customer loyalty, service quality strategy and marketing mix strategy on customer loyalty through KPR customer satisfaction at PT. Bank Central Asia Tbk Makassar Branch. To achieve these objectives, techniques of collecting data carried out through observation and distribution questionnaires by using data analysis techniques, namely descriptive analysis, validity and reliability testing, assumption classic tests, and path analysis. The results of this study proved that the service quality strategy and marketing mix strategy gave a positive and significant effect on customer satisfaction. Service quality strategy and marketing mix strategy gave a positive and significant influence on customer loyalty, the customers' satisfaction has a positive and significant effect on customer loyalty, customer satisfaction could mediate the effect between service quality strategy and marketing mix strategy on increasing customer loyalty at PT. Bank Central Asia, Tbk. Makassar Branch.